Perancangan Prototipe Perangkat Lunak Expert System Dengan Metode Backward Chaining Untuk Membantu Proses Pemeriksaan Antenatal Di Tingkat Pelayanan Dasar - S.M. Santi Winarsih; Retno Palupi (Universitas Boyolali, 2020)
Antenatal care at the Basic Service Level is defined antenatal checks will be undertaken to examine the circumstances of the mother and fetus at regular intervals, followed by an attempt correction of deviations found. The goal is to keep pregnant women can go through pregnancy, childbirth and post-partum properly and safely, and to produce a healthy baby.Procees Antenatal still done manually and is very dependent on the health workers so that the necessary software that can help this problem. The present study emphasizes the design of a prototype expert system software to assist in the level of antenatal examination of basic services.The purpose of this research is to make protitipe design software in order to help workers in antenatal care at the level of basic services.The method used in the design of a prototype expert system software that helps antenatal checks the method used in the design of a prototype expert system software to assist in the level of antenatal examination of basic services. The stages are done systematically in this study is a study phase began with a reference library to find supporters then gathered data, to identify and to determine the extent of the problem konseptualisiasi and experts involved, then formalize the knowledge base includes the manufacture of that relate to the topic, determining ie backward chaining inference method, followed by the drafting of a database, and then to design new prototype expert system software with backward chaining method that can assist antenatal examination in basic service level.